Organizational communication: a model applicable to the small business (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
Our premise is that a communication system based on a strategic plan is necessary for all types of organizations, including micro and small enterprises. We intend to analyze the communication system of a micro company dedicated to the provision of medical equipment in western Mexico with the following objectives: a) Emphasize the importance of communication in organizations, and the benefits that flow from it, b) propose a theoretical framework of communication in micro, small and medium enterprises (SMEs), c ) a diagnosis of communication in Health Systems (SS) d) To propose a communication model for SS. The methodology is the development of a conceptual model that culminates Nosnik productive communication. The model is tested by applying a series of surveys and interviews with key players in the company under study. The results highlighted the systematization of a model of organizational communication for small and medium enterprises to carry out a diagnosis of SS communication system and proposed a communication model for it. Among the findings highlighted that communication systems are essential for all types and sizes of organization. This exercise demonstrates the importance of communication in a micro-insert in a competitive market, which reaches international standards and move towards productive communication schemes or strategic raised, among others, by Nosnik (2000, 2003) and Corella Rebeil (2000)
Keywords: organizational communication; productive communication; small and medium enterprises